Murine eosinophil development and allergic lung eosinophilia are largely dependent on the signaling adaptor GRB2 - Willebrand, Ralf; Dietschmann, Axel; Nitschke, Lars; Krappmann, Sven; Vöhringer, David (European Journal of Immunology, 2018)
Eosinophils are innate effector cells associated with allergic inflammation. Their development and survival is largely dependent on IL-5 and the common beta chain (βc ) of the IL-5 receptor that serves as docking site for several proteins that mediate down-stream signaling cascades including JAK/STAT, PI3 kinase, NFκB, and RAS-MAP kinase pathways. The relative contribution of these signaling pathways for eosinophil development and homeostasis in vivo are poorly understood. Here, we investigated the role of GRB2, an adaptor protein that binds to βc and other proteins and elicits the RAS-MAP kinase pathway. By using GRB2 inhibitors and inducible deletion of the Grb2 gene in mouse eosinophils we demonstrate that GRB2 plays a critical role for development of eosinophils from bone marrow precursors. Furthermore, Aspergillus fumigatus-induced allergic lung eosinophilia was significantly reduced in mice with induced genetic deletion of Grb2. Our results indicate that GRB2 is important for eosinophil development in steady-state conditions and during allergic inflammation. Based on these findings pharmacologic GRB2 inhibitors may have the potential to dampen tissue eosinophilia in various eosinophil-associated diseases.
EVALuna2:36387

Phosphatidylinositol 3-Kinase (PI3K) Orchestrates Aspergillus fumigatus-Induced Eosinophil Activation Independently of Canonical Toll-Like Receptor (TLR)/C-Type-Lectin Receptor (CLR) Signaling - Dietschmann, Axel; Schrüfer, Sebastian; Westermann, Stefanie; Henkel, Fiona; Castiglione, Kirstin; Willebrand, Ralf; Adam, Jasmin; Ruland, Jurgen; Lang, Roland; Sheppard, Donald C.; Esser-Von-Bieren, Julia; Radtke, Daniel; et al. (Mbio, 2022)
Eosinophilia is associated with various persisting inflammatory diseases and often coincides with chronic fungal infections or fungal allergy as in the case of allergic bronchopulmonary aspergillosis (ABPA). Here, we show that intranasal administration of live Aspergillus fumigatus conidia causes fatal lung damage in eosinophilic interleukin-5 (IL-5)-transgenic mice. To further investigate the activation of eosinophils by A. fumigatus, we established a coculture system of mouse bone marrow-derived eosinophils (BMDE) with different A. fumigatus morphotypes and analyzed the secretion of cytokines, chemokines, and eicosanoids. A. fumigatus-stimulated BMDE upregulated expression of CD11b and downregulated CD62L and CCR3. They further secreted several proinflammatory mediators, including IL-4, IL-13, IL-18, macrophage inflammatory protein-1 alpha (MIP-1 alpha)/CC chemokine ligand 3 (CCL3), MIP-1 beta/CCL4, and thromboxane. This effect required direct interaction and adherence between eosinophils and A. fumigatus, as A. fumigatus culture supernatants or A. fumigatus mutant strains with impaired adhesion elicited a rather poor eosinophil response. Unexpectedly, canonical Toll-like receptor (TLR) or C-type-lectin receptor (CLR) signaling was largely dispensable, as the absence of MYD88, TRIF, or caspase recruitment domain-containing protein 9 (CARD9) resulted in only minor alterations. However, transcriptome analysis indicated a role for the PI3K-AKT-mTOR pathway in A. fumigatus-induced eosinophil activation. Correspondingly, we could show that phosphatidylinositol 3-kinase (PI3K) inhibitors successfully prevent A. fumigatus-induced eosinophil activation. The PI3K pathway in eosinophils may therefore serve as a potential drug target to interfere with undesired eosinophil activation in fungus-elicited eosinophilic disorders. IMPORTANCE Allergic bronchopulmonary aspergillosis (ABPA) is caused by the fungus Aspergillus fumigatus, afflicts about five million patients globally, and is still a noncurable disease. ABPA is associated with pronounced lung eosinophilia. Activated eosinophils enhance the inflammatory response not only by degranulation of toxic proteins but also by secretion of small effector molecules. Receptors and signaling pathways involved in activation of eosinophils by A. fumigatus are currently unknown. Here, we show that A. fumigatus-elicited activation of eosinophils requires direct cell-cell contact and results in modulation of cell surface markers and rapid secretion of cytokines, chemokines, and lipid mediators. Unexpectedly, this activation occurred independently of canonical Toll-like receptor or C-type lectin receptor signaling. However, transcriptome analysis indicated a role for the PI3K-AKT-mTOR pathway, and PI3K inhibitors successfully prevented A. fumigatus-induced eosinophil activation. The PI3K pathway may therefore serve as a potential drug target to interfere with undesired eosinophil activation in fungus-elicited eosinophilic disorders.
CRIS-Team WoS Importer:2022-06-24

PI3K signaling orchestrates eosinophil activation against Aspergillus fumigatus independently of canonical TLR/CLR signaling - Dietschmann, Axel; Schrüfer, Sebastian; Westermann, Stefanie; Henkel, F.; Castiglione, Kathrin; Willebrand, Ralf; Ruland, J.; Lang, Roland; Esser-Von-Bieren, J.; Radtke, Daniel; Krappmann, Sven; Vöhringer, David (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

Siglec-F Promotes IL-33-Induced Cytokine Release from Bone Marrow-Derived Eosinophils Independently of the ITIM and ITIM-like Motif Phosphorylation - Westermann, Stefanie; Dietschmann, Axel; Doehler, Daniela; Castiglione, Kirstin; Bochner, Bruce S.; Vöhringer, David; Radtke, Daniel (Journal of Immunology, 2022)
Eosinophils are potent innate effector cells associated mainly with type 2 immune responses elicited by helminths and allergens. Their activity needs to be tightly controlled to prevent severe inflammation and tissue damage. Eosinophil degranulation and secretion of inflammatory effector molecules, including cytokines, chemokines, and lipid mediators, can be regulated by activating and inhibitory receptors on the cell surface. In this study, we investigated the modulation of proliferation, apoptosis, gene expression, and cytokine/chemokine secretion from IL-33-activated Mus musculus eosinophils on cross-linking of the transmembrane receptor Sialic acid-binding Ig-like lectin F (Siglec-F). Siglec-F contains an ITIM plus an ITIM-like motif in its intracellular tail and is mainly regarded as an inhibitory and apoptosis-inducing receptor. In vitro costimulation of bone marrow-derived eosinophils with anti-Siglec-F and IL-33 compared with treatment with either alone led to enhanced STAT6 phosphorylation, stronger induction of hypoxia/glycolysis-related proinflammatory genes, and elevated secretion of type 2 cytokines (IL-4, IL-13) and chemokines (CCL3, CCL4) with only minor effects on proliferation and apoptosis. Using a competitive mixed bone marrow chimera approach with wild-type and Siglec-F-deficient eosinophils, we observed no evidence for Siglec-F-regulated inhibition of Aspergillus fumigates-elicited lung eosinophilia. Truncation of the Siglec-F cytoplasmic tail, but not mutation of the ITIM and ITIM-like motifs, ablated the effect of enhanced cytokine/chemokine secretion. This provides evidence for an ITIM phosphorylation-independent signaling pathway from the cytoplasmic tail of the Siglec-F receptor that enhances effector molecule release from activated eosinophils.
CRIS-Team WoS Importer:2022-03-04

STAT6-dependent deletion and trans-differentiation of alveolar macrophages during allergic airway inflammation - Ruhl, Andreas; Dietschmann, Axel; Murray, P. J.; Vöhringer, David (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

STAT6-induced production of mucus and resistin-like molecules in lung Club cells does not protect against helminth or influenza A virus infection - Ruhl, Andreas; Vieira Antao, Ana Isabel; Dietschmann, Axel; Radtke, Daniel; Tenbusch, Matthias; Vöhringer, David (European Journal of Immunology, 2023)
Airway epithelial cells contribute to a variety of lung diseases including allergic asthma, where IL-4 and IL-13 promote activation of the transcription factor STAT6. This leads to goblet cell hyperplasia and the secretion of effector molecules by epithelial cells. However, the specific effect of activated STAT6 in lung epithelial cells is only partially understood. Here, we created a mouse strain to selectively investigate the role of constitutively active STAT6 in Club cells, a subpopulation of airway epithelial cells. CCSP-Cre_STAT6vt mice and bronchiolar organoids derived from these show an enhanced expression of the chitinase-like protein Chil4 (Ym2) and resistin-like molecules (Relm-α, -β, -γ). In addition, goblet cells of these mice spontaneously secrete mucus into the bronchi. However, the activated epithelium resulted neither in impaired lung function nor conferred a protective effect against the migrating helminth Nippostrongylus brasiliensis. Moreover, CCSP-Cre_STAT6vt mice showed similar allergic airway inflammation induced by live conidia of the fungus Aspergillus fumigatus and similar recovery after influenza A virus infection compared to control mice. Together these results highlight that STAT6 signaling in Club cells induces the secretion of Relm proteins and mucus without impairing lung function, but this is not sufficient to confer protection against helminth or viral infections.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Aspergillus fumigatus; Club cell; Influenza a virus; Mucus; Nippostrongylus brasilienis; Relm-α; STAT6

Th2 cells promote eosinophil-independent pathology in a murine model of allergic bronchopulmonary aspergillosis - Dietschmann, Axel; Schruefer, Sebastian; Krappmann, Sven; Vöhringer, David (European Journal of Immunology, 2020)
Repeated inhalation of airborne conidia derived from the fungus Aspergillus fumigatus (Af) can lead to a severe eosinophil-dominated inflammatory condition of the lung termed allergic bronchopulmonary aspergillosis (ABPA). ABPA affects about 5 million individuals worldwide and the mechanisms regulating lung pathology in ABPA are poorly understood. Here, we used a mouse model of ABPA to investigate the role of eosinophils and T cell-derived IL-4/IL-13 for induction of allergic lung inflammation. Selective deletion of IL-4/IL-13 in T cells blunted the Af-induced lung eosinophilia and further resulted in lower expression of STAT6-regulated chemokines and effector proteins such as Arginase 1, Relm-α, Relm-β, and Muc5a/c. Eosinophil-deficient ΔdblGata mice showed lower IL-4 expression in the lung and the number of Th2 cells in the lung parenchyma was reduced. However, expression of the goblet cell markers Clca1 and Muc5a/c, abundance of mucin-positive cells, as well as weight gain of lungs were comparable between Af-challenged ΔdblGata and WT mice. Based on these results, we conclude that T cell-derived IL-4/IL-13 is essential for Af-induced lung eosinophilia and inflammation while eosinophils may play a more subtle immunomodulatory role and should not simply be regarded as pro-inflammatory effector cells in ABPA.
CRIS-Team Scopus Importer:2020-03-20
Keywords: allergy; Aspergillus fumigatus; eosinophils; IL-4/IL-13; lung inflammation

Th2-dependent disappearance and phenotypic conversion of mouse alveolar macrophages - Dietschmann, Axel; Ruhl, Andreas; Murray, Peter J.; Günther, Claudia; Becker, Christoph; Fallon, Padraic; Vöhringer, David (European Journal of Immunology, 2023)
Alveolar macrophages (alvMs) play an important role for maintenance of lung function by constant removal of cellular debris in the alveolar space. They further contribute to defense against microbial or viral infections and limit tissue damage during acute lung injury. alvMs arise from embryonic progenitor cells, seed the alveoli before birth, and have life-long self-renewing capacity. However, recruited monocytes may also help to restore the alvM population after depletion caused by toxins or influenza virus infection. At present, the population dynamics and cellular plasticity of alvMs during allergic lung inflammation is poorly defined. To address this point, we used a mouse model of Aspergillus fumigatus-induced allergic lung inflammation and observed that Th2-derived IL-4 and IL-13 caused almost complete disappearance of alvMs. This effect required STAT6 expression in alvMs and also occurred in various other settings of type 2 immunity-mediated lung inflammation or administration of IL-4 complexes to the lung. In addition, Th2 cells promoted conversion of alvMs to alternatively activated macrophages and multinucleated giant cells. Given the well-established role of alvMs for maintenance of lung function, this process may have implications for resolution of inflammation and tissue homeostasis in allergic asthma.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Allergic asthma; Alternatively activated macrophages; Alveolar macrophages; Aspergillus; Multinucleated giant cells; STAT6

The regulatory and transcriptional landscape associated with carbon utilization in a filamentous fungus - Wu, Vincent W.; Thieme, Nils; Huberman, Lori B.; Dietschmann, Axel; Kowbel, David J.; Lee, Juna; Calhoun, Sara; Singan, Vasanth R.; Lipzen, Anna; Xiong, Yi; Monti, Remo; Blow, Matthew J.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Filamentous fungi, such as Neurospora crassa, are very efficient in deconstructing plant biomass by the secretion of an arsenal of plant cell wall-degrading enzymes, by remodeling metabolism to accommodate production of secreted enzymes, and by enabling transport and intracellular utilization of plant biomass components. Although a number of enzymes and transcriptional regulators involved in plant biomass utilization have been identified, how filamentous fungi sense and integrate nutritional information encoded in the plant cell wall into a regulatory hierarchy for optimal utilization of complex carbon sources is not understood. Here, we performed transcriptional profiling of N. crassa on 40 different carbon sources, including plant biomass, to provide data on how fungi sense simple to complex carbohydrates. From these data, we identified regulatory factors in N. crassa and characterized one (PDR-2) associated with pectin utilization and one with pectin/hemicellulose utilization (ARA-1). Using in vitro DNA affinity purification sequencing (DAP-seq), we identified direct targets of transcription factors involved in regulating genes encoding plant cell wall-degrading enzymes. In particular, our data clarified the role of the transcription factor VIB-1 in the regulation of genes encoding plant cell wall-degrading enzymes and nutrient scavenging and revealed a major role of the carbon catabolite repressor CRE-1 in regulating the expression of major facilitator transporter genes. These data contribute to a more complete understanding of cross talk between transcription factors and their target genes, which are involved in regulating nutrient sensing and plant biomass utilization on a global level.
CRIS-Team Scopus Importer:2020-03-27
Keywords: DAP-seq; Nutrient; Plant biomass deconstruction; RNA-seq; Sensing; Transcriptional networks